Effects of cement, abutment surface pretreatment, and artificial aging on the force required to detach cantilever fixed dental prostheses from dental implants - Kappel, Stefanie; Rammelsberg, Peter; Rues, Stefan (The international journal of prosthodontics, 2017)
Stefanie Kappel, Dr Med Dent/Taras Chepura, Dentist/Marc Schmitter, Prof Dr Med Dent/Peter Rammelsberg, Prof Dr Med Dent/Stefan Rues, Dipl-Ing: Purpose: To examine the in vitro effects of different cements, abutment surface preconditioning, and artificial aging on the maximum tensile force needed to detach cantilever fixed dental prostheses (FDPs) from dental implants with titanium abutments. Materials and Methods: A total of 32 tissue-level implants were combined with standardized titanium abutments. For each test group, eight cantilever FDPs were fabricated using selective laser melting (cobalt-chromium [CoCr] alloy). The inner surfaces of the cantilever FDPs and half of the abutments were sandblasted and then joined by use of four different cements (two permanent and two semi-permanent) in two different amounts per cement. Subgroups were tested after either artificial aging (thermocycling and chewing simulation) or 3 days of water storage. Finally, axial pull off-tests were performed for each abutment separately. Results: Cement type and surface pretreatment significantly affected decementation behavior. The highest retention forces (approximately 1,200 N) were associated with sandblasted abutments and permanent cements. With unconditioned abutments, temporary cements (Fu < 100 N), as well as glass-ionomer cement (Fu ≈ 100 N), resulted in rather low retention forces. Zinc phosphate cement guaranteed high retention forces. After aging, retention was sufficient only for cementation with zinc phosphate cement and for the combination of sandblasted abutments and glass-ionomer cement. Conclusions: When glass-ionomer cement is used to fix cantilever FDPs on implants, sandblasting of standard titanium abutments may help prevent loss of retention. Retention forces were still high for FDPs fixed with zinc phosphate cement, even when the abutments were not pretreated. Use of permanent cements only, however, is recommended to prevent unwanted loosening of cantilever FDPs.
Gesehen am 25.06.2018